Nucleoside macrocycles formed by intramolecular click reaction: efficient cyclization of pyrimidine nucleosides decorated with 5'-azido residues and 5-octadiynyl side chains - Liu, Jiang; Leonard, Peter; Müller, Sebastian L.; Daniliuc, Constantin; Seela, Frank (Beilstein Journal of Organic Chemistry, 2018)
Copper(I)-promoted "click" cyclization in the presence of TBTA afforded nucleoside macrocycles in very high yields (≈70%) without using protecting groups. To this end, dU and dC derivatives functionalized at the 5-position of the nucleobase with octadiynyl side chains and with azido groups at the 5’-position of the sugar moieties were synthesized. The macrocycles display freely accessible Watson–Crick recognition sites. The conformation of the 16-membered macrocycle was deduced from X-ray analysis and 1H,1H-NMR coupling constants. The sugar conformation (N vs S) was different in solution as compared to the solid state.
Keywords: click cyclization; conformation; macrocycles; nucleosides; X-ray